The world food situation: an overview - von Braun, Joachim (International Food Policy Research Institute, 2005)
While 2004 and 2005 were promising in terms of renewed attention to reducing hunger, the world still faces the large and familiar problems of widespread hunger and malnutrition. In addition, it is becoming clearer that hidden hunger due to micronutrient deficiencies is widespread. At the same time, over-consumption and the chronic disease problems that accompany it are creeping into poor families...And it is time to think beyond 2015. Different sets of policies will be needed to end hunger rather than to cut it in half. Global and national actors will need to target the poorest countries and people, particularly the rural poor, to reach those who will have been left behind by the MDG process. We will need new insights into the complex interactions between agriculture, health, and lifestyles, and to adopt a stronger focus on gender issues. We will need to invest in appropriate insurance systems and social security policies. Bio- and info- technological innovations based on science for the poorest and marginalized will be critical. And natural resource constraints will need to be addressed to safeguard against new food security threats. We must push ourselves even further to develop and implement solutions and policies to achieve food and nutrition security for the poorest of the poor and those most afflicted by hunger—for the other half of the MDGs.